CLUSTER ANALYSIS OF PARAMETRIC GRADATION OF CONTROL MEASUREMENTS OF CLOTHING FOR WOMEN OF LARGE SIZES - SLAVINSKA, ALLA; SYROTENKO, OKSANA; MYTSA, VICTORIIA; DOMBROVSKA, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The preservation of the functional properties of the sewing product is regulated by technical regulatory documentation. The insufficient filling of the market with an assortment of clothes for women of large sizes is explained by the complexity of the geometry of the body surface, which is regulated by different approaches to the classification of sizes in the current anthropometric standards. The study of the dimensional variability of the range of large-sized figures in clusters of the main and additional dimensions of outerwear was carried out taking into account the synchronization of complete groups. Harmonization of the typology was carried out by cross-comparing the limitations of the size scale taking into account the type of figure M in the table of dimensions of the technical documentation. Body prototype M, height 168 cm, chest girth 110, 116 cm was chosen based on the frequency of occurrence in 10 models of women’s dresses. Graphical interpretation of absolute deviations characterizes the synchronicity of preservation of anthropometric commensurability at all levels of application of regulatory documentation. Numerical series of displacement values of 9 control measurements were formed for standardizing the basis of deviations for 4 regulatory documents based on the principle of combining in pairs. Confirmed synchronicity of preservation of anthropometric proportionality at all levels of application of regulatory documentation: figure-structure-product.